Prognostic significance of coronary arteriography. - Balcon, Raphael (Acta Médica Portuguesa, 1980)
An index of severity of coronary artery disease is described which takes into account the site, severity and number of all lesions in the coronary arteries. A percentage figure is computed with low percentages indicating severe disease. Ten year follow-up for 1050 medically treated patients are given. During the period of observation the overall mortality rate was 6.3%. 68% of deaths occurring in the first year and 97% in the first five years. Survival curves are drawn for five years and cindicate significant differences in survival between the four quartikes of the coronary index. In particular, a high risk group is described with a coronary index of 25% or less. Left ventricular abnormalities further decrease the survival rates.